Approach to remote routing computation and lookup in parallel network simulation - HAO Zhi-yu; YUN Xiao-chun; ZHANG Hong-li (Tongxin xuebao)
A new method which computes remote routing based on the border routers,was presented and finds the appropriate route by comparing the length of routing.It effectively reduces the size of remote routing table,and improves the efficiency of network simulation.Compared with PDNS,it reduces 90 percent of the size of the remote routing table,saves 20 percent of the memory needed during the initialization,and 25 percent of the simulation time.